FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI IKAN DI DESA MENGU KECAMATAN PAGA KABUPATEN SIKKA - Igansius Mbasa; Reyna Virginia Nona (Program Studi Ekonomi Pembangunan Universitas Flores, 2021)
This study aims to determine how the influence of capital, labor, length of time at sea, and climate on fish production and to determine how much influence capital, labor, length of fishing, and climate have on fish production. The population in the study was 283 people and the sample was 74 people. This research uses questionnaire and interview methods and is processed by multiple linear regression analysis of the SPSS version 21 program. The results showed that there was an effect of the variables of capital, labor, length of fishing and climate on fish production in Mbengu Village. The results of the test simultaneously were 822.979 and the significance was 0.000. The partial test results obtained the variable value of capital 0.983 and the significance was 0.329, the value of the power variable Work time of 0.732, the significance is 0.467 and the length of time at sea is 0.47.779 and the significance is 0.000. Partially the length of time at sea has a significant effect on fish production and the contribution of the independent variable to the dependent variable (Y) is 97.1%.